Inversion in the published genetic map of linkage group VII - E Kouzminova; E U Selker (Fungal Genetics Reports, 1999)
In the course of cloning the dim-2 gene of Neurospora crassa we found that the published map of LG VII has an inversion of a segment extending from for to un-10K. Direct physical mapping confirmed that the gene order in this region should be wc-1, for, frq, oli, un-10.